UNDANG-UNDANG PERLINDUNGAN KONSUMEN: ATURAN HUKUM YANG DISESUAIKAN DENGAN NILAI PANCASILA (Jurnal Magister Hukum Perspektif, 2022)
The ideology of Pancasila that was developed as the basis for making Law Number 8 of 1999 concerning Consumer Protection is a thought that is relevant to the goal of creating a welfare state. Based on the background above, the formulation of the problem in this article is how to regulate the rule of law that is adjusted to the value of Pancasila in the Consumer Protection Law. The research method in writing this article is to use normative legal research methods. The results of the research in this article are by looking at the fifth precept, we can know that the goal is to refine the values of Pancasila as an element needed to form a unified view of life (way of life or weltanschauung) this is objectively Pancasila has met the requirements to be declared as a philosophy of life system (philosophy of life). Keywords: Pancasila Ideology, Consumer Protection, Welfare State